Azithromycin-liposomes as a novel approach for localized therapy of cervicovaginal bacterial infections - VaniÄ‡,Å½eljka; Rukavina,Zora; Manner,Suvi; Fallarero,Adyary; Uzelac,Lidija; Kralj,Marijeta; AmidÅ¾iÄ‡ KlariÄ‡,Daniela; Bogdanov,Anita; Raffai,TÃmea; Virok,DezsÅ‘ Peter; FilipoviÄ‡-GrÄiÄ‡,Jelena; Å kalko-Basnet,NataÅ¡a (International Journal of Nanomedicine, 2019)
Å½eljka VaniÄ‡,1 Zora Rukavina,1 Suvi Manner,2 Adyary Fallarero,3 Lidija Uzelac,4 Marijeta Kralj,4 Daniela AmidÅ¾iÄ‡ KlariÄ‡,1 Anita Bogdanov,5 Tímea Raffai,5 DezsÅ‘ Peter Virok,5 Jelena FilipoviÄ‡-GrÄiÄ‡,1 Nataša Škalko-Basnet61Department of Pharmaceutical Technology, Faculty of Pharmacy and Biochemistry, University of Zagreb, 10000 Zagreb, Croatia; 2Pharmaceutical Sciences Laboratory, Faculty of Science and Engineering, Åbo Akademi and University of Helsinki, 20520 Turku, Finland; 3Division of Pharmaceutical Biosciences, Pharmaceutical Biology, Faculty of Pharmacy, University of Helsinki, 00014 Helsinki, Finland; 4Department of Molecular Medicine, RuÄ‘er BoškoviÄ‡ Institute, 10000 Zagreb, Croatia; 5Department of Medical Microbiology and Immunobiology, University of Szeged, 6720 Szeged, Hungary; 6Drug Transport and Delivery Research Group, Department of Pharmacy, Faculty of Health Sciences, University of Tromsø the Arctic University of Norway, 5037 Tromsø, NorwayBackground: Efficient localized cervicovaginal antibacterial therapy, enabling the delivery of antibiotic to the site of action at lower doses while escaping systemic drug effects and reducing the risk of developing microbial resistance, is attracting considerable attention. Liposomes have been shown to allow sustained drug release into vaginal mucosa and improve delivery of antibiotics to bacterial cells and biofilms. Azithromycin (AZI), a potent broad-spectrum macrolide antibiotic, has not yet been investigated for localized therapy of cervicovaginal infections, although it is administered orally for the treatment of sexually transmitted diseases. Encapsulation of AZI in liposomes could improve its solubility, antibacterial activity, and allow the prolonged drug release in the cervicovaginal tissue, while avoiding systemic side effects.Purpose: The objective of this study was to develop AZI-liposomes and explore their potentials for treating cervicovaginal infections.Methods: AZI-liposomes that differed in bilayer elasticity/rigidity and surface ...